(untitled) (Web of Teachers: Inderscience Research, 2025)
Tonsillitis is an inflammation of the tonsils, often accompanied by a sore throat, difficulty swallowing and fever. This disease can be either acute or chronic, caused by a bacterial or viral infection. Scientific thought can be compared to a perpetual motion machine, which, contrary to the laws of physics, does not stop for a moment. It penetrates into the most hidden corners of the universe, expanding the boundaries of knowledge and opening new horizons. Acute tonsillitis, also known as angina, is manifested by a sharp deterioration in the condition, enlargement of the lymph nodes and the formation of purulent plugs. The chronic form is characterized by periodic exacerbations, bad breath and a feeling of discomfort in the throat.